Future Directions for Early Childhood Prevention of Mental Disorders: A Road Map to Mental Health, Earlier. Issue 3 (4th May 2019) - Wakschlag, Lauren S.; Roberts, Megan Y.; Flynn, Rachel M.; Smith, Justin D.; Krogh-Jespersen, Sheila; Kaat, Aaron J.; Gray, Larry; Walkup, John; Marino, Bradley S.; Norton, Elizabeth S.; Davis, Matthew M.
Abstract : Mental disorders are the predominant chronic diseases of youth, with substantial life span morbidity and mortality. A wealth of evidence demonstrates that the neurodevelopmental roots of common mental health problems are present in early childhood. Unfortunately, this has not been translated to systematic strategies for improving population-level mental health at this most malleable neurodevelopmental period. We lay out a translational Mental Health, Earlier road map as a key future direction for prevention of mental disorder. This paradigm shift aims to reduce population attributable risk of mental disorder emanating from early life, by preventing, attenuating, or delaying onset/course of chronic psychopathology via the promotion of self-regulation in early childhood within large-scale health care delivery systems. The Earlier Pillar rests on a "science of when to worry" that (a) optimizes clinical assessment methods for characterizing probabilistic clinical risk beginning in infancy via deliberate incorporation of neurodevelopmental heterogeneity, and (b) universal primary-care-based screening targeting patterns of dysregulated irritability as a robust transdiagnostic marker of vulnerability to life span mental health problems. The core of the Healthier Pillar is provision of low-intensity selective intervention promoting self-regulation for young children with developmentally atypical patterns of irritability within an implementation science framework in pediatric primary care to ensure highest population impact and sustainability. These Mental Health, Earlier strategies hold much promise for transforming clinical outlooks and ensuring young children's mental health and well-being in a manner that reverberates throughout the life span.